A microencapsulated feed additive containing organic acids and botanicals has a distinct effect on proliferative and metabolic related signaling in the jejunum and ileum of broiler chickens - Johnson, Casey N.; Arsenault, Ryan J.; Piva, Andrea; Grilli, Ester; Swaggerty, Christina L. (Frontiers in Physiology, 2023)
Well designed and formulated natural feed additives have the potential to provide many of the growth promoting and disease mitigating characteristics of in-feed antibiotics, particularly feed additives that elicit their effects on targeted areas of the gut. Here, we describe the mechanism of action of a microencapsulated feed additive containing organic acids and botanicals (AviPlus®P) on the jejunum and ileum of 15-day-old broiler-type chickens. Day-of-hatch chicks were provided ad libitum access to feed containing either 0 or 500 g/MT of the feed additive for the duration of the study. Fifteen days post-hatch, birds were humanely euthanized and necropsied. Jejunum and ileum tissue samples were collected and either flash frozen or stored in RNA-later as appropriate for downstream applications. Chicken-specific kinome peptide array analysis was conducted on the jejunum and ileum tissues, comparing the tissues from the treated birds to those from their respective controls. Detailed analysis of peptides representing individual kinase target sites revealed that in the ileum there was a broad increase in the signal transduction pathways centering on activation of HIF-1α, AMPK, mTOR, PI3K-Akt and NFκB. These signaling responses were largely decreased in the jejunum relative to control birds. Gene expression analysis agrees with the kinome data showing strong immune gene expression in the ileum and reduced expression in the jejunum. The microencapsulated blend of organic acids and botanicals elicit a more anti-inflammatory phenotype and reduced signaling in the jejunum while resulting in enhanced immunometabolic responses in the ileum.